MANAGEMENT OF INCREASED LEARNING MOTIVATION SPIRITUAL GUIDANCE IN OPTIMIZING STUDENT LEARNING OUTCOMES IN MADRASAH - Rozi, Fathor; Qomariyah, Tis'atul (Managere: Indonesian Journal of Educational Management, 2022)
This study aims to know and analyze the management of increasing learning motivation based on spiritual guidance in optimizing learning outcomes at MIS Islamiyah kertosono gading probolinggo. Information was obtained from several informants from the head of the ibtidaiyah madrasah, teachers, students and guardians. Then to select and determine informants in this study, researchers used purposive sampling techniques. Data collection techniques in this study used content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The data analysis technique used in this study is interactive model analysis. The stages in analyzing data in this study are data reduction, data presentation, and conclusions. The results in management research on increasing motivation to learn based on spiritual guidance are carried out by Strengthening the quality of human resources, spiritual direction, and cultivating. The implications obtained by the management of increasing learning motivation based on spiritual guidance impact the growth of enthusiasm for learning in students to be more active in learning.